Cointegration of Interdependencies Among Capital Markets of Chosen Visegrad Countries and Germany - Marcin Faldzinski; Adam P. Balcerzak; Tomas Meluzin; Michal Bernard Pietrzak; Marek Zinecker (Institute of Economic Research (IER), 2016)
Identification of linkages among capital markets is crucial for forming policies that take into account risk associated with international financial markets in-terdependencies. Thus, the aim of the article is to analyse interdependencies among capital markets of Germany, Poland, Czech Republic and Hungary. The research hypothesis was given as follows: There is a similar course and changes in the inter-dependencies among capital markets of Germany and the markets of the mentioned countries of the Visegrad Group. In the research a DCC-GARCH model was applied. The model allowed to estimate conditional correlations that indicate strength of the interrelationship among the markets. Then, the cointegration analysis of the conditional correlations was conducted. The proposed econometric procedure allowed to verify the research hypothesis. It confirmed that the capital markets of Germany, Poland, Czech Republic and Hungary are characterised with similar long-term path. Additionally, the research showed that changes in the direction and strength of the interrelationships among the studied markets are determined by the German capital market in the long-term, which is a leader in the region.
Keywords: G15; C58; 330; cointegration of interdependencies among capital markets; conditional correlation; DCC-GARCH model; conditional variance